Pengaruh Lingkungan Kerja dan Disiplin Kerja terhadap Kinerja Karyawan pada PT. Yasmin Amanah Media - Eny Nur Haryani, (Jurnal Publikasi Ilmu Manajemen, 2025)
This research aims to analyze the influence of the work environment and work discipline on employee performance at PT. Yasmin Amanah Media. This research uses quantitative methods by distributing questionnaires to 42 employees and the data is analyzed using validity tests, reliability tests, classical assumption tests, hypothesis tests, and coefficient of determination tests with the help of the SPSS version 25 application. The results of the research show that the work environment and work discipline are together have a positive and significant effect on employee performance with an R Square value of 0.572 which indicates 57.2% or 57% (value after rounding). A safe and comfortable work environment and good work discipline can achieve employee performance that is as expected by the company.